75 Parental perspective about the health and development of their extremely preterm child. (29th October 2021) - Milette, Audrey-Anne; Richter, Lindsay; Bourque, Claude-Julie; Janvier, Annie; Robson, Kate; Church, Paige Therrien; Synnes, Anne; Luu, Thuy
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Preterm birth outcome studies and clinical follow-up have traditionally focused on neurodevelopment. We previously showed in a selected sample of parents that they also valued other types of outcomes. Objectives: This study aimed to validate these findings in a more diverse cohort by examining parental perspectives about the positive and negative aspects of their very preterm child's health and development in relation to level of neurodevelopment impairment (NDI). Design/Methods: Parents of children born < 29 weeks gestational age in 2016-2018 and seen at two Canadian neonatal follow-up clinics were invited to complete an online survey about their level of agreement with statements about their child's health, development, and well-being. Parental responses in relation to their child's level of NDI were examined using Kruskal-Wallis and chi-square for trends tests. Results: 199 parental responses were obtained for 165 children (65% of eligible children). Of these children, 52%, 27% and 21% had, respectively, no, mild to moderate, and severe NDI. Development was the most common source of concerns (49%), followed by the child's future (35%), and physical health (35%). Parents of children with severe NDI were more likely to express concerns than those with mild to moderate or no NDI. Parents rated their child's health relatively high with a median score of 8/10 (range 3-10). Children with no NDI were given higher scores than those with NDI (p = 0.004). Regardless of level of NDI, almost all parents agreed with their child being happy (p = 1.000) and having a positive personality (p = 0.207). Figure 1 shows that parental concerns increased with level of NDI. Conclusion: Parents of preterm children have a balanced perspective on their child's outcome. Integrating their views when developing core sets of important outcomes for neonatal follow-up is critical.